Spatial sero-survey of respiratory tract viral infections in cattle at the wildlife-livestock interface in the Mnisi communal farming area of South Africa - Jansen van Vuuren, M. (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.